Development of Guided Inquiry-Based Module to Improve Students Understanding in Complex Analysis: A Case of STKIP Muhammadiyah Sungai Penuh - Nofyta Arlianti; Al Ikhlas (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: This development research aims to develop a Complex Analysis module with a guide inquiry approach that is valid, practical, and effective in terms of contents and constructs. The focus of this study is the use of modules that can lead to interest in learning and creative thinking because they are easy to understand and like to use. The subject of this study was the seventh semester students of mathematics education at STKIP Muhammadiyah Sungai Penuh. Data collected using The development model is 4D from Thiagarajan, but only 3D is used, for the deployment phase it is not done because research is not aimed at generalizing. The results showed that the module with an inquiry guide approach in the Complex Analysis lecture was practical, based on the results of the description and data analysis, the level of student activity during the lecture process was active students, and learning outcomes were obtained more than 70% of students got scores over 65. Keywords: module, guided inquiry approach, mathematics learning.